Penerapan Ilmu Administrasi dalam Kegiatan di Biro Organisasi SETDA Kalteng Application of Administrative Science in Activities at the Central Kalimantan Regional Secretariat Organization Bureau - Ajeng Hijriatul Aulia; Jamilah Jamilah; Risna Wendy Wiraganti; Khusnul Khatimah; Diva Fitaloka Oktaviani; Muhammad Luthfi Setiarno Putera; Muhammad Norhadi (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study examines the application of administrative science in the activities of the Organization Bureau at the Regional Secretariat of Central Kalimantan Province. The research background is based on the importance of bureaucratic reform, demands for transparency, and the need for institutional strengthening at the regional level. The purpose of this study is to describe how administrative science is applied in the bureau’s activities and its impact on strengthening governance. The research method used was participatory action research (PAR), involving students and bureau staff through the stages of planning, action, observation, and reflection. The findings show a significant contribution in terms of improving the efficiency of document preparation, accelerating data digitalization, and fostering collaborative awareness within the bureau. Moreover, social changes emerged, such as the establishment of regular evaluation practices, openness to technology, and the rise of informal leadership among staff. These results emphasize that collaboration between universities and government bureaus can accelerate bureaucratic transformation toward more adaptive and responsive governance.